Perbedaan Pengetahuan Tentang Hipertensi Puskesmas Tanjung Baru Kabupaten OKU - Eva Yustati; Willy Astriana; Arda Dinata (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
The prevalence of hypertension continues to increase in line with lifestyle changes such as smoking, physical inactivity and psychosocial stress. The World Health Organization (WHO) in 2018 showed that around 1.13 billion people in the world suffer from hypertension. This means that 1 in 3 people in the world are diagnosed with hypertension. The method used in this study used a pre-experimental design. The population in this study were all Prolanis participants in a total of 90 participants. The sample of this research is Accidental Sampling consisting of 25 respondents. Univariate Analysis Statistical results showed that the average knowledge before counseling was 5.76 and after counseling 7.9. Means the difference in knowledge about hypertension before and after counseling is 2.2. Statistical test results obtained p value 0.000. This means that there is a difference in the average value of knowledge about hypertension before and after counseling is carried out. The conclusion in this study is that there are differences in the knowledge of respondents before and after being given counseling about hypertension at the Tanjung Baru Health Center in 2022